EFFECT OF HEALTH EDUCATION OF SAFETY RIDING USING AUDIOVISUAL MEDIA ON KNOWLEDGE, ATTITUDES AND SUBJECTIVE NORMS OF JUNIOR HIGH SCHOOL STUDENTS IN SAMARINDA INDONESIA - Wahnadita Rahman; Dina Lusiana Setyowati; Riza Hayati Ifroh (Public Health of Indonesia)
Background: Traffic accidents are the main cause of death for adolescents aged 16-19 years. Teenagers in junior high school age are very vulnerable to traffic accidents. The importance of giving safety riding health education to junior high school students is to prepare them in the active phase of riding in an effort to prevent traffic accidents.